Pembelajaran Terpadu dan Urgensinya dalam Pengembangan Karakter Anak Sekolah Dasar - Elizar Elizar (Universitas Muhammadiyah Kotabumi, 2019)
Integrated learning models is a learning that is associated with an increased ability and characters of student in elementary school. School as one of the means and facitating role in shaping the young generation and motivate the studens to give to become savvy genaration, independent, creative, and innovative.To anticipate the occurrence of inefficiency in implementing the learning program should be planned with the best. Prior to the implementation of a learning program conducted there are some things that must be considered, planning before setting up learning programs need, designing and organizing learning evaluation, is used as an effort to obtain information to assess the success of a program. One of some efforts that could be done to improve students’ skill, as prospective teachers, in implementing an active learning was that by implementing integrated learning. It covered modelling a lecturer as a model in implementing integrated learning in the class and it integratef active learning models in fragmented, connected, sequenced, shared, webbed, threaded, integrated, immersed, and networked